2021
DOI: 10.1007/s00268-021-05958-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 Restrictions on Demographics and Outcomes of Patients Undergoing Medically Necessary Non‐Emergent Surgeries During the Pandemic

Abstract: Background The COVID-19 pandemic has resulted in large-scale healthcare restrictions to control viral spread, reducing operating room censuses to include only medically necessary surgeries. The impact of restrictions on which patients undergo surgical procedures and their perioperative outcomes is less understood. Methods Adult patients who underwent medically necessary surgical procedures at our institution during a restricted operative period due to the COVID-19 pandemic (March 23-April 24, 2020) were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 57 publications
(63 reference statements)
3
8
2
Order By: Relevance
“…In our study, we found that more patients had statutory insurance during the lockdown period. This is contrary to a study performed at the Hospital of the University of Pennsylvania, which found that a higher proportion of patients undergoing medically necessary surgeries during the pandemic had private insurance instead of statutory insurance [32] . The reasons may lie in the very different insurance systems.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, we found that more patients had statutory insurance during the lockdown period. This is contrary to a study performed at the Hospital of the University of Pennsylvania, which found that a higher proportion of patients undergoing medically necessary surgeries during the pandemic had private insurance instead of statutory insurance [32] . The reasons may lie in the very different insurance systems.…”
Section: Discussioncontrasting
confidence: 99%
“… 3 4 Medically necessary non-emergent surgeries were more likely to be performed on White patients with private insurance compared with any other group during the pandemic. 3 …”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, patients from under-represented racial groups also suffered worse outcomes for non-COVID-19-related conditions highlighting pre-existing disparities in healthcare access and differences in ability to socially distance at work and home 3 4. Medically necessary non-emergent surgeries were more likely to be performed on White patients with private insurance compared with any other group during the pandemic 3…”
Section: Introductionmentioning
confidence: 99%
“…Hospitals nationwide canceled or postponed nonessential operations during the height of the pandemic to minimize viral transmission and preserve medical resources. 1 Patient lives were upended by shifts to virtual schooling, closure of childcare facilities, and increasing unemployment rates. Additionally, there were concerns the pandemic will widen surgical disparities for populations who have historically faced difficulties in accessing and receiving surgical care.…”
mentioning
confidence: 99%
“…The coronavirus pandemic has brought an explosion in surgical literature on the implications of social determinants of health and race/ethnicity on access to surgical care and clinical outcomes such as mortality. Hospitals nationwide canceled or postponed nonessential operations during the height of the pandemic to minimize viral transmission and preserve medical resources 1 . Patient lives were upended by shifts to virtual schooling, closure of childcare facilities, and increasing unemployment rates.…”
mentioning
confidence: 99%